2019
DOI: 10.1002/advs.201900030
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Staphyloxanthin in Methicillin‐Resistant Staphylococcus aureus Potentiates Killing by Reactive Oxygen Species

Abstract: Confronted with the severe situation that the pace of resistance acquisition is faster than the clinical introduction of new antibiotics, health organizations are calling for effective approaches to combat methicillin‐resistant Staphylococcus aureus (MRSA) infections. Here, an approach to treat MRSA through photolysis of staphyloxanthin, an antioxidant residing in the microdomain of S. aureus membrane, is reported. This photochemistry process is uncovered through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 50 publications
2
92
0
1
Order By: Relevance
“…1B). As a result, the unsaturated tail of STX, the nine conjugated C=C double bonds, is decomposed or truncated, as confirmed by mass spectrometry (17). In contrast, when we blocked STX biosynthesis in S. aureus by knocking down CrtM, namely S. aureus ΔCrtM, its colony turns colorless and shows no detectable peaks for all three Raman bands, confirming that these Raman bands are exclusively from STX (Fig.…”
Section: Pulsed Blue Laser Photolysis Of Staphyloxanthinmentioning
confidence: 55%
See 3 more Smart Citations
“…1B). As a result, the unsaturated tail of STX, the nine conjugated C=C double bonds, is decomposed or truncated, as confirmed by mass spectrometry (17). In contrast, when we blocked STX biosynthesis in S. aureus by knocking down CrtM, namely S. aureus ΔCrtM, its colony turns colorless and shows no detectable peaks for all three Raman bands, confirming that these Raman bands are exclusively from STX (Fig.…”
Section: Pulsed Blue Laser Photolysis Of Staphyloxanthinmentioning
confidence: 55%
“…For example, disassembly of FMM could be further extended to revive chloramphenicol, as its resistance primarily due to the overexpression of norA-encoded multidrug-resistance efflux pumps within the microdomains (35). As STX has the antioxidant function to shield MRSA from attacks by ROS, effective STX photolysis could further render MRSA susceptible to oxidative host killing including macrophage cells and neutrophils (17). Similar to daptomycin, the modulation on cell membrane fluidity via laser treatment can facilitate non-oxidative host defense of cationic antimicrobial peptides (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experiments have demonstrated that the staphyloxanthin (STX) carotenoid pigment within methicillin-resistant S. aureus (MRSA) is capable of undergoing photolysis when exposed to 460 nm light. This results in the formation of pores within the membrane of MRSA that not only increase the susceptibility of MRSA to reactive oxygen species, but also resensitize MRSA to conventional antibiotics the bacteria was previously resistant to (25,26).…”
Section: Introductionmentioning
confidence: 99%